2003
DOI: 10.1029/2002rs002670
|View full text |Cite
|
Sign up to set email alerts
|

A change of microwave radiation from the ocean surface induced by air‐sea temperature difference

Abstract: We investigate microwave radiation from the ocean surface to observe changes in microwave radiation for various air‐sea temperature differences by using data of the Special Sensor Microwave/Imager 19 GHz and the TRMM Microwave Imager 19 and 10 GHz. To this end, we developed a method of removing the atmospheric effect. Under strong winds exceeding 7m/s, atmospheric‐effect‐removed temperatures of both vertical and horizontal polarizations increase, and the ratio of the V/H increase in stable condition is less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The KS model used by SMOS results in smaller biases at many temperatures but lead to very large and temperature dependent biases in cold waters. Our results with the KS model are consistent with assessments of microwave radiometers at higher frequencies which found that corrections to TB at the cold end (0 • C) needed to be larger than at the warm end (30 • C) by 0.5 K and 3.7 K at 6 GHz [55] and 37 GHz [56] respectively. It is therefore critical to improve the current dielectric constant models.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The KS model used by SMOS results in smaller biases at many temperatures but lead to very large and temperature dependent biases in cold waters. Our results with the KS model are consistent with assessments of microwave radiometers at higher frequencies which found that corrections to TB at the cold end (0 • C) needed to be larger than at the warm end (30 • C) by 0.5 K and 3.7 K at 6 GHz [55] and 37 GHz [56] respectively. It is therefore critical to improve the current dielectric constant models.…”
Section: Discussionsupporting
confidence: 88%
“…In waters colder than 5 • C, the KS model exhibits very problematic performances. Considering the large errors it produces (>1 psu), and the fast change in the bias with SST (1 psu over a 5 • C range), it appears that the accuracy of the KS model is questionable below 5 • C. This result is consistent with the assessment of microwave radiometers at higher frequencies which found an increase in the KS model bias in cold waters [55,56]. It is doubtful that all the SST-dependent error can be attributed to the dielectric constant model, as other factors can commingle their error and its dependence on SST (e.g., roughness model).…”
Section: Discussionsupporting
confidence: 73%
“…Unstable atmospheric conditions enhance the generation and the thickness and coverage of foam and whitecaps. Although the phenomenon of increases in observed radiances under unstable conditions has been studied (Monahan and O'Muircheartaigh, 1986;Reul and Chapron, 2003;Shibata, 2003Shibata, , 2007Wei, 2013), no emissivity model is yet available that includes the effect of atmospheric stability on foam coverage.…”
Section: Biases In Cold Sectorsmentioning
confidence: 99%
“…Previous studies have shown that the sensitivity to the ocean wind at horizontal polarization is larger than that at vertical polarization [7,40]. The study of [15] only used 6.9 and 10.7 GHz horizontal polarization (hereafter, 6H and 10H) data from AMSR-E to retrieve wind speed inside hurricanes.…”
Section: Wind Speed Retrieval Modelmentioning
confidence: 99%